Multi2Sim: A Simulation Framework to Evaluate Multicore-Multithreaded Processors - Ubal, Rafael; Sahuquillo, Julio; Petit, Salvador; Lopez, Pedro (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2007)
Current microprocessors are based in complex designs, integrating different components on a single chip, such as hardware threads, processor cores, memory hierarchy or interconnection networks. The permanent need of evaluating new designs on each of these components motivates the development of tools which simulate the system working as a whole. In this paper, we present the Multi2Sim simulation framework, which models the major components of incoming systems, and is intended to cover the limitations of existing simulators. A set of simulation examples is also included for illustrative purposes.